2013
DOI: 10.5861/ijrsll.2014.661
|View full text |Cite
|
Sign up to set email alerts
|

The effect of explicit teaching of apologies on Persian EFL learners’ performance: When e-communication helps

Abstract: The present study was conducted to examine the effect of explicit teaching of the speech act of apology on learning and recognition of Persian EFL learners with the help of e-communication through exchange of e-mails. The participants of the study consisted of 60 upper-intermediate EFL learners majoring in English Literature and Translation who were divided into two groups: a) the explicit teaching group and b) the implicit teaching group. Accordingly, instruction on various apology situations was provided and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 30 publications
1
14
0
5
Order By: Relevance
“…From the above results we can claim that implementing pedagogical intervention in the EFL classroom had a positive effect on both the amount and type of apology formulas used by learners immediately after being engaged in the instructional treatment. These findings therefore confirm previous ILP research supporting the fact that instruction does make a difference in the pragmatic realm (see Jeon and Kaya 2006;Takahashi 2010;Taguchi 2011Taguchi , 2015 for a review), and are in line with previous studies that have particularly examined the teachability of the speech act of apologies in FL settings (Eslami-Rasekh et al, 2004;Eslami-Rasekh and Eslami-Rasekh, 2008;Eslami-Rasekh and Mardani, 2010;Birjandi and Derakhshan, 2013;Simin et al, 2014;Derakhshan and Eslami-Rasekh, 2015).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…From the above results we can claim that implementing pedagogical intervention in the EFL classroom had a positive effect on both the amount and type of apology formulas used by learners immediately after being engaged in the instructional treatment. These findings therefore confirm previous ILP research supporting the fact that instruction does make a difference in the pragmatic realm (see Jeon and Kaya 2006;Takahashi 2010;Taguchi 2011Taguchi , 2015 for a review), and are in line with previous studies that have particularly examined the teachability of the speech act of apologies in FL settings (Eslami-Rasekh et al, 2004;Eslami-Rasekh and Eslami-Rasekh, 2008;Eslami-Rasekh and Mardani, 2010;Birjandi and Derakhshan, 2013;Simin et al, 2014;Derakhshan and Eslami-Rasekh, 2015).…”
Section: Resultssupporting
confidence: 80%
“…Finally, Simin et al (2014) investigated the role of instruction in developing learners' pragmatic awareness on recognition and production of Alicia Martínez-Flor DOI: http://dx.doi.org/10. 12795/elia.2016.i16.02 apologies with the help of e-communication through exchange of e-mails.…”
Section: Interventional Studies On Apologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that Iranian EFL learners have continually faced with the challenges to communicate in L2 and they have mostly failed in their daily interactions have inspired SLA researchers to explore the status of EFL learners' L2 pragmatic competence in EFL classroom and examine learners' pragmatic knowledge development (Rajabi & Farahian, 2013;Simin et al, 2014). Moreover, the research literature in pragmatic performance has shown that the studies done (Alfattah, 2009;Jebahi, 2013;Gu, 2014) were mostly intercultural in nature and compared the pragmatic performance of native speakers with non-native speakers with regard to the realization of speech acts strategies focusing on learners' pragmalinguistic knowledge.…”
Section: Introductionmentioning
confidence: 99%